(untitled) (Diametros, 2016)
The paper presents an argument for respecting conscientious refusals based on the Thomistic account of conscience; the argument does not employ the notion of right. The main idea is that acting against one’s conscience necessarily makes the action objectively wrong and performed in bad faith, and expecting someone to act against his or her conscience is incompatible with requiring him or her to act in good faith. In light of this idea I also examine the issue of obligations imposed on objectors as well as the claims that conscientious objectors should change their profession.